EFSIENSI PEMBUATAN BIODISEL DARI MINYAK GORENG BEKAS MELALUI PROSES NETRALISAI DAN TRANSESTERIFIKASI - Antonius Prihanto T. A. Bambang Irawan (Universitas Slamet Riyadi, 2018)
The purpose of this research is to improve the efficiency of making biodiesel from used cookingoil. Used cooking oil has a high fatty acid content that is high enough that when processed intobiodiesel through transesterifikasi will occur blocking the reaction of biodiesel formation. Blocking thereaction results in doubling methanol demand and the separation of biodiesel becomes difficult due tothe formation of soap so that the resulting yield decreases, so the method is less efficient. The processof free fatty acid removal through neutralization takes less time. The neutralization process is alsocheaper because it requires only a small amount of NaOH so that the making of biodiesel from cookingoil through the neutralization-transesterification process is more efficient in terms of time and cost.To obtain the best transesterification process condition, the effect of temperature variation (30 oC, 40oC, 50 oC, 60 oC, 70 oC) on yield of biodiesel produced, variation of KOH catalyst concentration(0.75%, 1%, 1, 25%, 1.5%, 1.75%) on the yield of biodiesel produced and the effect of variation ofmethanol-oil molar ratio (6: 1; 7: 1; 8: 1; 9: 1; 10: 1) on biodiesel yield which is produced from usedcooking oil. The results showed at 60 ° C, KOH 1% catalyst concentration and a 6: 1 molar methanoloilratio resulted in a maximum biodiesel yield of 87.3%.Keywords: efficiency, biodiesel, used cooking oil